AB0864 THE EFFECT OF ZOLEDRONIC ACID ON CHARCOT NEUROARTHROPATHY. (June 2019) - Boussaid, Soumaya; Bettaieb, Hiba; Jemmali, Samia; Ajlani, Houda; Rekik, Sonia; Sahli, Hela; Cheour, Elhem; Euch, Mohamed El
Abstract : Background: The Charcot foot syndrome is a serious neuroarthropathy that may threaten the functional prognosis of diabetic patient. Some studies had emphasized the beneficial effect of bisphosphonates such as pamidronate and alendronate on the reduction in bone turnover markers in this disease. Though, the use of Zoledronic acid in the treatment of Charcot foot was only evaluated in two clinical trials and its efficacy remains controversial (1, 2). Objectives: The aim of this study was to investigate the clinical and radiological efficacy of Zoledronic acid in patients with diabetes and acute Charcot neuroarthropathy. Methods: A prospective 2-year follow-up study was carried out on eight patient with type 2 diabetic and acute Charcot neuroarthropathy. All our patients had a physical examination and podiatry exam. The stage of the neuroarthropathy has been assessed according to the clinical and the radiographic findings (Eichenholtz Classification). All patients were assigned to intravenous infusions of 4 mg Zoledronic acid. Results: The mean age of the study group was 61.4 +/- 4.5 years. The mean age of the onset of foot pain was 18.3 +/- 1.5 years. The midfoot involvement was bilateral in 6 patients and unilateral in the other two. A biological inflammatory syndrome was found in 3 patients with a mean erythrocyte sedimentation rate (ESR) level at 43 mm after one hour. Foot X-rays were abnormal at all cases. The clinical outcomes at one month after Zoledronic acid infusions were the complete disappearance of acute symptoms in 6 patients and the improvement of the pain in one patient with a decreased Visual Analogue Scale (VAS) for pain by 30%. One patient had a persistence of the pain (VAS for pain at 5mm). A radiological Control was performed after 6 months for 5 patients. All of them had bone consolidation and remineralization. Conclusion: Our study showed that the Zoledronic acid, given as a single dose, had a beneficial effect on clinical and radiological features in diabetic patients with acute Charcot neuroarthropathy.Despite our encouraging outcomes, further prospective and randomized studies are needed to confirm our preliminary results. References: [1] Pakarinien TK, Laine HJ, Mäenpää H, et al. the effect of zoledronic acid on the Clinical Resolution of Charcot Neuroarthropathy. Diabetes Care. 2011;34:1514-16. [2] Bharath R, Bal A, Shanmuga S, et al. A comparative study of zoledronic acid and once weekly Alendronate in the management of acute Charcot arthropathy of foot in patients with diabetes mellitus.Indian J Endocrinol Metab. 2013 Jan-Feb; 17(1): 110–116 Disclosure of Interests: None declared